Dose–response effect between the number of long COVID symptoms and the use of different health services - Yohana Pereira Vieira; Juliana Quadros Santos Rocha; Vanise dos Santos Ferreira Viero; Bruno Pereira Nunes; Luiz Augusto Facchini; Suele Manjourany Silva Duro; Rosália Garcia Neves; César Fernández-de-las-Peñas; Mirelle de Oliveira Saes (Scientific Reports)
Abstract This study aims to identify the use of health services by individuals with long COVID residing in South Brazil 6 months after the acute phase of a SARS-CoV-2 infection. A cross-sectional cohort study of individuals who survived coronavirus disease was conducted in Rio Grande, Brazil. The participants were asked about their use of health services during the 6–10 months following recovery from SARS-CoV-2 infection. Data on the overall use of primary healthcare services, general practitioner services, emergency services, specialist doctors’ services, and specialized services were collected. Individuals with long COVID reported more frequent use of primary healthcare services, emergency services, specialist doctors’ services, and specialized services than those without long COVID. The musculoskeletal, neurological, and respiratory symptoms of long COVID were associated with frequent use of primary healthcare services, whereas the neurological, digestive, and respiratory symptoms were associated with frequent use of emergency services. Finally, the use of specialist doctors’ services and specialized services was more frequent in participants with neurological symptoms than in those without these symptoms. Individuals with long COVID used more healthcare services than those without long COVID in South Brazil. Participants with a greater number of symptoms used more health services than those with fewer symptoms. Healthcare services use depends on the type of the long COVID symptoms. Health services in Brazil need to be reorganized and adapted to provide adequate treatment and care to people with long COVID.